Ecuador - Development Policy Review : Growth, Inclusion and Governance - The Road Ahead - World Bank (Washington, DC, 2013)
This Development Policy Review (DPR) for Ecuador compliments the policy notes already produced and is medium-term oriented, focused on strategic priorities as perceived from the Bank's own vision of Ecuador. The report looks at the political economy from both a historical and economic perspective. It adds an assessment of the implementation of the economic, social, and governance agenda during the first year of current administration and makes proposals for its fine-tuning. The DPR contains an overview of the major development outcomes including macroeconomic performance, fiscal policy and public debt sustainability, the social gap, governance, corruption, long-term growth trends, and competitiveness. A development agenda is laid out along with medium term outlook and risks.